Peningkatan Kemampuan Tenaga Akuntansi dalam Pelaporan Dana Bantuan Operasional Sekolah (Bos) pada Sekolah Menengah Pertama Islam Tahfizhul Qur’an Kabupaten Kubu Raya - Adithya, Rizky Adithya; Suherma, Linda; Andriana, Susan; Riyani, Yani; Mardiah, Kartawati; Riyadhi, Baidillah; Kurniasih, Ninik; Rynandi, Oscar; Haryati, Haryati; Andini, Risky Suci (Politeknik Negeri Pontianak, 2024)
The School Operational Assistance Fund (BOS) is intended for schools to overcome the burden of education costs in order to complete twelve years of compulsory education. The government began to report BOS funds online and integrated. The development of government technology accommodates BOS recipients to report the use of funds in a timely manner. This community service program scheme is to assist in reporting the BOS Fund in Islamic Junior High Schools. The main problems of SMPI Tahfizhul Qur'an Kubu Raya Regency are: 1). Lack of IT skills in Accounting personnel for making online reports. 2). There is an unreported misuse of funds. The solution offered to overcome problems regarding BOS fund management at SMP Tahfizhul Qur'an Kubu Raya Regency is basic and secondary training on Microsoft Excel and financial accounting for online reporting. This PPM activity will improve IT and accounting capabilities for accounting personnel in the field of financial reporting of BOS funds both offline and online which are measured after the implementation of activities.